Analisis Pengaruh Intellectual Capital Dan Spiritual Capital Terhadap Pengelolaan Keuangan UMKM Kabupaten Tana Toraja - Trevi Claudia Lestari; Jemi Pabisangan Tahirs; Yohanis Lotong Ta'dung (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Trevi Claudia Lestari (2023). This study aims to determine the effect Intellectual Capital And Spiritual Capital on MSME financial management in Tana Toraja Regency . This study used a questionnaire distributed to SMEs in Regency Tana Torajan . Sampling using non-probability sampling with a purposive sampling approach . The data analysis technique used is linear regression analysis double . From the test results known Intellectual Capital (X1) And Spiritual Capital (X2) is influential positive And significant to MSME Finance (Y) . In the partial test results it is known that the value of t is calculated variable Intellectual Capital (X1) 2,762 is greater than t table 2,010 and the value is sig. 0.000 _ < 0.05 . On variable Spiritual Capital ( X2) 2,579 is greater than t table 2,010 and the sig value. 0.003 < 0.05 . While the test results of the coefficient of determination are known Intellectual Capital (X1) And Spiritual Capital (X2) has an effect of 58.2% and the remaining 41.8% is influenced by other variables outside of this study. Results test simultaneous show mark FcountÂ  5,102 more big from Ftable 4050 with sig . 0.004 < 0.05, then can is known that variable Intellectual Capital (X1) and Spiritual Capital (X2) is influential in a manner simultaneous to MSME Finance (Y).